The Discovery of Circadian Rhythm of Feeding Time on Digestive Enzymes Activity and Their Gene Expression in Sinonovacula constricta Within a Light/Dark Cycle - Liu, Yanzi; Yao, Hanhan; Zhou, Tingting; Lin, Zhihua; Dong, Yinghui (Frontiers in Marine Science, 2021)
The circadian rhythm has a great influence on the growth, metabolism, and development of animals, but little is known about the circadian rhythm of shellfish. Understanding of the feeding rhythm is of great significance to increase the yield of razor clam Sinonovacula constricta, an economically important bivalve mollusk. The aim of this experiment is to study the effects of circadian rhythm of feeding time on digestive enzymes activities and their gene expression in S. constricta within a light/dark cycle. The present results showed that circadian rhythm of feeding rate (FR) was highly associated with digestive enzyme activities and relative expression of related genes. The highest values of FR were basically observed in the evening from 00:00-02:00 and 06:00-08:00, which were significantly higher than those values in the daytime from 12:00-14:00 and 18:00-20:00.The digestive enzymes activities displayed the highest values at 02:00 and 08:00, and the lowest at 14:00 and 20:00. Among them, cellulase and pepsin were found to have significantly different activities (P<0.05), rather than amylase and lipase. Notably, the relative expression of digestive enzyme genes shared the similar pattern with the activities of digestive enzymes. The highest values of relative expression of amylase (AMY), lipase (LIP), cellulase (CEL) and pepsin (PEP) were found at 02:00 and 08:00 at night, while the lowest values were found at 14:00 and 20:00 during the day. It is therefore suggested that the changed expression of biological clock genes may regulate the process from feeding to digestion. Furthermore, it might be better to feed at night to reduce cultivating cost and increase economic benefits in the farming industry of S. constricta.